Investigation of fly-bacteria’s association on decomposing tissues and antimicrobial evaluation of fly larvae native excretions/secretions - Ahmad Azani Othman; Muhammad Syafiq Mohd Nasarudin; Nurul Narisya Othman; Azwandi Ahmad (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
The interaction between flies and microbes on decomposing tissue is mediated by a vast community of bacteria. Currently, the knowledge of this relationship is limited by technological barriers. Besides, the antimicrobial activity of native excretions or secretions (NES) of fly larvae is important to be evaluated. The objective of this preliminary study is to understand the fly-bacteria association on decomposing tissue through bacteria identification along with the antimicrobial activity of NES. Two fish baits (Rastrelliger brachysoma) weighing 120 grams each were installed at two locations in Universiti Teknologi MARA, Puncak Alam Campus, Selangor, Malaysia from 17th April 2021 to 24th April 2021. Specimens of adult flies, larvae, pupae, and swabs of the bait surface were taken daily. The bacteria colonies were isolated from four different locations: blowflies’ external surface, blowflies' internal microbiome, larvae external surface, and bait surface. A total of 23 flies were identified represented by four species from three families. Chrysomya megacephala (Family: Calliphoridae) was the most abundant species followed by Sarcophaga sp. (Family: Sarcophagidae), Ophyra spinigera (Family: Muscidae), and Atherigona orientalis (Family: Muscidae). However, Sarcophaga sp. larvae were the dominant larva species. Culture-based bacterial investigation showed that both Gram-positive and Gram-negative bacteria were present on the external surface and the internal microbiome of Ch. megacephala. Meanwhile, temporal changes of the Gram-negative bacteria group from non-lactose fermenter to lactose fermenter were observed on larvae external surface samples as well as samples from the decomposing bait. The investigation of NES collected failed to show any antimicrobial activity. A larger sample size is recommended for the future antimicrobial properties of NES studies. In conclusion, the data obtained from this preliminary study can be used as a basic direction for future studies. This study can be extended by using metagenomic methods to understand more about the bacteria-fly association.